(3JWhQ GdSdWI GdJTQjYjI aj Ohd GdNdjL GdYQHj (B: s (3OQGSI ebGQfI (B/ s - (3MejO EHQGgje CMeO GdMeGOjs; (3jMji YHO GdYRjR GdLeds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2014)
(3JJfGhd GdOQGSI JfhY CTcGd GdeLGdS GdfjGHjI HOhd GdNdjL GdYQHi, EP JJHfi HYVgG GdTcd GdeROhL, Ci Cf GdHQdeGf jJchf dOjgG ef eLdSjf Ch ZQaJjf, CeG GdHYV GdCNQ aCHbi Ydi GdTcd GdCMGOj ddeLdS, ceG JHGjf gPg GdOhd aj CSdhH ONhd GdfGFH eHfi GdHQdeGf MjK aVd HYVgG GdGfJNGH, hGdHYV GdCNQ Xd eYJekOG Ydi GdJYjjf ef LGfH GdSdWI GdJfajPjI, MjK Cf GNJdGa GdeLGdS GdfjGHjI GdNdjLjI aj JTcjdgG dG YdGbI dg HbhI Ch VYa GNJUGUGJgG, anJnchf GdHQdeGf ef eLdSjf dG jYfi Cfg Ph JCKjQ Cbhi eeG dh cGf CMGOkjG, HOdjd MGdI eLdS GdCeI GdchjJj GdPj jYJHQ HENJUGUGJg GdOSJhQjI GdLgI GdJTQjYjI GdMbjbjI aj GdHdGO, ai GdebGHd fLO Cf eLdS YeGf hGdechf ef eLdSj GdOhdI hGdThQj, jYJHQ LgI GSJTGQjI HMJI, JDOj GNJUGUGJ jZdH YdjgG GdLGfH GdGLJeGYj, HeYfi Cf GNJUGUGJg JOhQ aj adc GdNOeGJ GdGLJeGYjI GdJj JbOe ddeLJeY YeheG(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe (B2014.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdeLGdS GdJTQjYjIs; (3GdSdWI GdJTQjYjI s; (3GdaUd Hjf GdSdWGJs; (3GSJbdGd GdeDSSI GdJTQjYjIs; (3GdeLGdS GdfjGHjIs; (3Ohd GdNdjL GdYQHi s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOSJhQjs